International research networks: Determinants of country embeddedness - Holger Graf; Martin Kalthaus (Friedrich Schiller University Jena, 2016)
We analyze the evolution of the international collaboration network in photovoltaic research. Using data on scientific publications for the period 1980-2015, we apply social network analysis to trace the evolution of the global network of countries and national research networks of organizations. Our objective is to identify the determinants of countries' international research embeddedness by looking at national policies and structural properties of the national research networks. We observe a steady increase of publications and collaboration within the global research network. While there is a small group of countries that remains central throughout all years, several countries emerge and catch up while others lose their relative position.We find that cohesion and connectedness of the national system positively affect research output as well as international embeddedness, whereas centralized systems are less embedded. Policy, especially demand side instruments, has a positive effect on publication output and embeddedness.
Keywords: L14; O31; O38; Q42; 330; bibliographic data; instrument mix; international collaboration; photovoltaics; research network